Meningkatkan Kosa Kata, Pengucapan Kata, dan Motivasi Belajar Bahasa Inggris Siswa Melalui Penerapan Metode Pembelajaran Total Physical Responses [Increasing Vocabulary, Pronunciation, and motivation to Study English Through Implementation of Total Physical Responses] - Sukandi, Steffina (Jurnal Teropong Pendidikan, 2022)
Mastering English language is very important because it is the most spoken language in global interaction. In order to master English, early age linguistic education is required. Therefore, the most suitable method used in this research is the Total Physical Responses (TPR), which emphasizes on vocabulary, pronunciation, and motivation to study English. The purposes of this research are: 1) to increase English vocabulary by using the TPR teaching method in Kindergarten A at Ehipassiko School BSD; 2) to increase English pronunciation by using the TPR teaching method in Kindergarten A Ehipassiko School BSD; 3) to increase motivation to study English by using the TPR teaching method in Kindergarten A Ehipassiko School BSD. This research was conducted in Kindergarten A Ehipassiko School BSD with  participants of 18 students, consists of 8 boys and 10 girls. The type of this research is pre-experimental research. The results showed an increased vocabulary, pronunciation, and motivation to study English through the method of TPR. It can be seen from the results of the N-Gain, vocabulary 0.755 was in the high category, the pronunciation in the medium category was 0.45 and 0.54 for motivation which is fall into the medium category. Based on the results of this research can be concluded that the teaching of English through the TPR teaching method can increase vocabulary, pronunciation, and motivation to study English.